ANALISIS RUTE PENGANGKUTAN SAMPAH KOTA MANADO DENGAN PENDEKATAN VEHICLE ROUTING PROBLEM (VRP) - Andre Lasut; Friska Makalew; Prudensy Opit (Jurnal Ilmiah Realtech, 2019)
Waste collection and transportation is a problem that currently being faced by cities in Indonesia, especially in the city of Manado. Manado is one of the major cities that produces 2,064 m of waste per day. In 2018, Manado was given a title as one of the dirtiest major cities in Indonesia by the Ministry of Environment and Forestry (KLHK) in the assessment of Adipura. This is due to the over capacity of the final disposal site (TPA) and the incapability of each TPA to implement the sanitary landfile system. The purpose of this research is to determine the efficiency of waste transportation in the city of Manado, especially in the watershed area (DAS). This research focuses on the transport points of the watershed area, namely: Bailang Bridge, Megawati Bridge, Kalimas, Tugu Lilin, Yellow Bridge, God Bless Park, Freshmart Bahu, Shoulder B ridge and Regional Police Complex. The model used to solve the problem in thisresearch is the Vehicle Routing Problem (VRP). The result of the total minimum of vehicle mileage is 81.4 km. Sensitivity analysisby adding three scenarios is completed in order to analyze the shortest distance using different routes. Based on the final results,we found that scenario 2 generates the minimum vehicle mileage of 73.8 km.